Constructing Soft Perovskite–Substrate Interfaces for Dynamic Modulation of Perovskite Film in Inverted Solar Cells with Over 6200 Hours Photostability. Issue 28 (17th August 2022) - Lv, Wenxuan; Hu, Zhaoying; Qiu, Wei; Yan, Dongdong; Li, Meicheng; Mei, Anyi; Xu, Ligang; Chen, Runfeng
Abstract: High‐performance perovskite solar cells (PSCs) depend heavily on the quality of perovskite films, which is closely related to the lattice distortion, perovskite crystallization, and interfacial defects when being spin‐coated and annealed on the substrate surface. Here, a dynamic strategy to modulate the perovskite film formation by using a soft perovskite–substrate interface constructed by employing amphiphilic soft molecules (ASMs) with long alkyl chains and Lewis base groups is proposed. The hydrophobic alkyl chains of ASMs interacted with poly(triarylamine) (PTAA) greatly improve the wettability of PTAA to facilitate the nucleation and growth of perovskite crystals, while the Lewis base groups bound to perovskite lattices significantly passivate the defects in situ. More importantly, this soft perovskite–substrate interface with ASMs between PTAA and perovskite film can dynamically match the lattice distortion with reduced interfacial residual strain upon perovskite crystallization and thermal annealing owing to the soft self‐adaptive long‐chains, leading to high‐quality perovskite films. Thus, the inverted PSCs show a power conversion efficiency approaching 20% with good reproducibility and negligible hysteresis. More impressively, the unencapsulated device exhibits state‐of‐the‐art photostability, retaining 84% of its initial efficiency under continuous simulated 1‐sun illumination for more than 6200 h at elevated temperature (≈65 °C). Abstract : A dynamic modulation strategy is developed to fabricate high‐quality perovskite films by constructing soft perovskite‐substrate interfaces. As a result, the unencapsulated device shows state‐of‐the‐art photostability, maintaining 84% initial efficiency under continuous simulated 1‐sun illumination for more than 6200 h.